A Multiscale Study of the Role of Environmental Variability on the Diversity and Abundance of Rock Pool Communities - Reid, Lesley (My University, 2003)
One of the main goals of ecological research is to understand the factors that determine how communities are structured over both space and time. However, our understanding of any system is largely a function of the scale at which we make our observations. Thus, the mechanisms that determine patterns in community structure are likely to change depending on the scale of observation. This thesis explores how environmental variability affects community structure and species performance, and how the resulting patterns change as a function of scale. Specifically, I asses the role of variability in temperature, oxygen, pH, and chloride, on species richness, abundance, diversity, and species performance, at three observational scales: micro-spatial, local temporal, and landscape-temporal scales, in 49 natural erosional rock pool microcosms, located on the northern coast of Jamaica. I found that while environmental variability was not a primary determinant of species richness or abundance, it did play a role in determining species compositions in the pools. I also show that community patterns are strongly affected by the scale of observation. Recognizing scale-dependent changes in community patterns is a prerequisite for predicting the consequences of changes in ecological systems induced by variability in abiotic factors.
The Role of Environmental Variability on Diversity
Keywords: rock pool communities; environmental variability; multiscale study